Effect of index HIV self-testing for sexual partners of clients enrolled in antiretroviral therapy (ART) programs in Malawi: A randomized controlled trial. - Kathryn Dovel; Kelvin Balakasi; Khumbo Phiri; Frackson Shaba; Ogechukwu Agatha Offorjebe; Sundeep K Gupta; Vincent Wong; Eric Lungu; Brooke E Nichols; Tobias Masina; Anteneh Worku; Risa Hoffman; et al. (PLoS Medicine, 2023)
Background HIV testing among the sexual partners of HIV-positive clients is critical for case identification and reduced transmission in southern and eastern Africa. HIV self-testing (HIVST) may improve uptake of HIV services among sexual partners of antiretroviral therapy (ART) clients, but the impact of HIVST on partner testing and subsequent ART initiation remains unclear. Methods and findings We conducted an individually randomized, unblinded trial to assess if an index HIVST intervention targeting the partners of ART clients improves uptake of testing and treatment services in Malawi. The trial was conducted at 3 high-burden facilities in central and southern Malawi. ART clients attending HIV treatment clinics were randomized using simple randomization 1:2·5 to: (1) standard partner referral slip (PRS) whereby ART clients were given facility referral slips to distribute to their primary sexual partners; or (2) index HIVST whereby ART clients were given HIVST kits + HIVST instructions and facility referral slips to distribute to their primary sexual partners. Inclusion criteria for ART clients were: ≥15 years of age, primary partner with unknown HIV status, no history of interpersonal violence (IPV) with partner, and partner lives in facility catchment area. The primary outcome was partner testing 4-weeks after enrollment, reported by ART clients using endline surveys. Medical chart reviews and tracing activities with partners with a reactive HIV test measured ART initiation at 12 months. Analyses were conducted based on modified intention-to-treat principles, whereby we excluded individuals who did not have complete endline data (i.e., were loss to follow up from the study). Adjusted models controlled for the effects of age and marital status. A total of 4,237 ART clients were screened and 484 were eligible and enrolled (77% female) between March 28, 2018 and January 5, 2020. A total of 365 participants completed an endline survey (257/34 index HIVST arm; 107/13 PRS arm) and were included in the final analysis (78% female). Testing coverage among sexual partners was 71% (183/257) in the index HIVST arm and 25% (27/107) in the PRS arm (aRR: 2·77, 95% CI [2·56 to 3·00], p ≤ 0.001). Reported HIV positivity rates did not significantly differ by arm (16% (30/183) in HIVST versus 15% (4/27) in PRS; p = 0.99). ART initiation at 12 months was 47% (14/30) in HIVST versus 75% (3/4) in PRS arms; however, index HIVST still resulted in a 94% increase in the proportion of all partners initiating ART due to higher HIV testing rates in the HIVST arm (5% partners initiated ART in HVIST versus 3% in PRS). Adverse events including IPV and termination of the relationship did not vary by arm (IPV: 3/257 index HIVST versus 4/10 PRS; p = 0.57). Limitations include reliance on secondary report by ART clients, potential social desirability bias, and not powered for sex disaggregated analyses. Conclusions Index HIVST significantly increased HIV testing and the absolute number of partners initiating ART in Malawi, without increased risk of adverse events. Additional research is needed to improve linkage to HIV treatment services after HIVST use. Trial registration ClinicalTrials.gov, NCT03271307, and Pan African Clinical Trials, PACTR201711002697316.